The Voyage of Tinospora Cordifolia (Guduchi)From Vedic to Modern Era: A Review - Dalai, Sujit Kumar; Mohapatra, Brahmanand; Dwivedi, Laxmikant (Asian Journal of Pharmaceutical Research and Development, 2013)
Tinospora cordifolia (Guduchi or Amrita) is popularly known in the Indian system of medicine as Giloe and has been in traditional use for several centuries in the treatment of fever, leprosy, asthma, anorexia, jaundice, diabetes, chronic diarrhea & dysentery, gout, skin-infections, irritability of stomach etc. It is mentioned in Ayurvedic literature as a constituent of several Ayurvedic compound preparations like Amritarista, Guduchyadi Modaka, Samsamani vati, Guduchyadi lauha, Pnachatikta ghrita and Balaguduchyadi taila etc has been used in general debility, dyspepsia, fever, urinary diseases and skin diseases etc also. This paper presents an exploration of critical and comparative review on morphology, variety, chemical properties, therapeutic properties and their various uses from Vedic to Modern era.